High-commitment work systems and employee voice: A multilevel and serial mediation approach inside the black box. Issue 4 (3rd June 2019) - Zhang, Junwei; Akhtar, Muhammad Naseer; Zhang, Yajun; Rofcanin, Yasin
Abstract : Purpose: Although scholars have suggested that employees often carefully consider social contexts before enacting voice, few studies have explored whether firms foster employee voice behavior by adopting a set of systematic HR practices, namely, high-commitment work systems (HCWS). By integrating the literature on HCWS and voice, the purpose of this paper is to explore the mechanisms of how HCWS utilization influences employee voice. Design/methodology/approach: The authors adopted multilevel analyses with HLM software to examine the research hypotheses. The authors collected data from a sample of 290 employees and 58 line managers from 11 software design and development firms in China. Findings: HCWS utilization positively affected employee-experienced HCWS which enhanced psychological safety and perceived organizational support, and in turn employee voice behavior. In addition, HCWS utilization positively influenced employee-experienced HCWS, and subsequently increased voice efficacy. However, contrary to the expectations, voice efficacy was not related to employee voice. Originality/value: The study is the first to integrate research on HCWS and voice. By building on the theory of planned behavior, the authors provide new insights into the relationship between HCWS utilization and employee voice and inspire researchers to elucidate other explanatory mechanisms in this link.